Soil Solution Analysis With Untargeted GC–MS—A Case Study With Different Lysimeter Types - Ueberschaar, Nico; Lehmann, Katharina; Meyer, Stefanie; Zerfass, Christian; Michalzik, Beate; Totsche, Kai Uwe; Pohnert, Georg (Frontiers in Earth Science, 2021)
Surface-sourced organic compounds in infiltrating waters and percolates are transformed during their belowground passage. Biotic and abiotic processes thereby lead to continuously changing chemical environments in subsurface compartments. The investigation of such transformations of organic compounds aims for tracing subsurface fluxes as well as biotic and abiotic activity. To collect samples of soil solution, different kinds of lysimeters are available, spanning simple free-draining devices that sample water based on gravimetric flow and tension lysimeters allowing for approximating natural hydraulic conditions. Protocols for untargeted analytical profiling of organic soil solution constituents are scarce. We report here a solid phase extraction followed by GC-MS analysis, utilizing two long-term sampling devices in the Hainich Critical Zone Exploratory in Thuringia, Germany. In addition, we introduce a new lysimeter constructed exclusively from inert materials that allows for obtaining samples with little background signals in GC-MS. Polyvinylchloride (PVC)-based lysimeters introduce substantial background signals from plasticizers. We show how these contaminants can be lowered during data analysis using chemometric background removal. Applying multivariate statistics for data analysis, we demonstrate the ability for monitoring of several sugars, fatty acids and phenolic acids at the topsoil-subsoil boundary and even beyond, via an untargeted analytical approach. Statistical tools facilitated the detection of differences in chemical signatures at three different land use sites. Data mining methods for metabolomics led to the identification of 3-carboxyphenylalanin as biomarker for a pasture site. The combined approach is suitable for the collection and extraction of topsoil and subsoil solution for untargeted metabolomics under near-natural flow conditions.